2018
DOI: 10.2174/1871522218666180608114536
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Apheresis in Metabolic Syndrome

Abstract: Background:The metabolic syndrome unites three pathologies of the person – obesity, arterial hypertension and diabetes. In recent years the progressing of such distribution covering from 2.5% to 3.8% of the population with increase twice each 10-15 years is noted. Even at maintenance of level of sugar at diabetes accumulation of the secondary metabolites breaking small vessels isn't excluded. At the same time many life-endangering complications develop.Objective:To identify the possibilities of plasmapheresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 106 publications
2
3
1
Order By: Relevance
“…There was no significant difference in expression of visfatin in placental tissues between the two groups (P>0.05). It indicates that AGEs and IL-6 are highly expressed in placental tissues of GDM parturients, which is consistent with the studies of Voinov (30), and Wang et al (31). In this study, the expression of APN in placental tissues of GDM patients was low, indicating that there was abnormal regulation of adipokines in placenta.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There was no significant difference in expression of visfatin in placental tissues between the two groups (P>0.05). It indicates that AGEs and IL-6 are highly expressed in placental tissues of GDM parturients, which is consistent with the studies of Voinov (30), and Wang et al (31). In this study, the expression of APN in placental tissues of GDM patients was low, indicating that there was abnormal regulation of adipokines in placenta.…”
Section: Discussionsupporting
confidence: 91%
“…The results of Dutta et al (40) showed that oxidative stress was associated with cell cycle arrest and fetal membrane oxidative injury, which jointly determined adverse pregnancy outcomes and were important factors for premature rupture of membranes and spontaneous premature birth. Studies on the relationship between AGE level and perinatal outcome in pregnant women with GDM have shown that high expression of AGEs is a risk factor for abnormal perinatal outcome in GDM (30). However, whether the AGEs, adipocytokines and oxidative stress levels can be used as important indicators to predict the pregnancy outcome with GDM requires further studies by expanding the number of samples.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the increased mortality with TPE in COVID-19 patients who have diabetes is not clear because plasma exchange has been shown to be beneficial not only in the treatment of SARS-CoV-2 but also in reducing complications of metabolic syndrome, particularly severe hypertriglyceridemia and the micro-vascular complications associated with type 2 diabetes. 16,17 In contrast to our study, Fernandez et al, demonstrated therapeutic plasma exchange as effective rescue therapy in 4 patients with multiple comorbidities, including type 2 diabetes mellitus, who had failed treatment with conventional treatment options such as antiviral agents. 18 A potential reason for the statistically insignificant results reported by our study is a small sample size, which can lead to more type II errors and low statistical power.…”
Section: Discussioncontrasting
confidence: 99%
“…It is necessary to detoxicate organism with removal pathological products resulting from virus reactivation to break through the course of the disease and to prevent complications. For this purpose, apheresis is the most effective therapy in removal pathological products and all components incompetent humoral immunity [20].…”
Section: Discussionmentioning
confidence: 99%